Manual Material Handling: A Classification Scheme. (2016) - Rajesh, R.
Abstract: Ergonomic evaluation of Manual Material Handling (MMH) has largely been based on task analysis approach where the job are broken down into simpler tasks and studied. But there is lack of clarity in the use of terms defining various MMH activities. The challenge in classifying MMH arises because of the dependence of man-machine interaction on multiple worksystem characteristics. This paper presents a classification scheme for MMH tasks. Towards making a classification scheme the work system characteristics are examined and the important dimensions from those are identified that are able to differentiate the nature of MMH exposure. Suitable examples for each class are presented. The methods for collecting biomechanical and physiological responses, and nature of ergonomic analysis required are discussed. A qualitative judgment on exposure magnitude and measurement cost is made. Finally, critical issues and scope for research is presented.